2-deoxy-D-glucose mitigates Citrobacter rodentium and dibenzazepine-induced gastrointestinal damage and colitis: novel implications of 2-DG polypharmacopea. (3rd April 2023) - Ahmed, Ishfaq; Verma, Amit; Umar, Shahid; Papineni, Rao V. L.
Abstract: Purpose: Citrobacter rodentium (CR) infection coupled with blocking Notch/Wnt signaling via γ-secretase inhibitor dibenzazepine (DBZ) disrupts the gastro-intestinal (GI) barrier and induces colitis, akin to ionizing radiation (IR)-induced GI-injury. We investigated the effects of 2-deoxy-D-glucose (2-DG) to ameliorate the CR-DBZ-induced GI damage. Materials and methods: NIH:Swiss outbred mice were inoculated with 10 9 CFUs of CR orally. DBZ was administered intraperitoneally (10 μ M/kg b.wt; for 10 days 2 days post-CR infection). Mice were fed with 0.4% 2-DG (w/v) daily in drinking water. For microbiota depletion, antibiotics (Abx), 1 g/l metronidazole, and 0.2 g/l ciprofloxacin were administered for 10 days in drinking water. Oxidative stress, survival assay, colonic crypt hyperplasia, Notch/Wnt downstream signaling, immunomodulation, and bacterial dysbiosis were measured. Results: We show that real-time visualization of reactive oxygen species (ROS) is similar during CR-induced colonic infection and IR-induced GI-damage. The histology revealed that dietary 2-DG mitigates CR + DBZ-induced colitis and improves survival compared with CR + DBZ alone. These changes were phenocopied in Abx-treated mice. Both 2-DG and Abx reduced dysbiosis, increased proliferation, inhibited pro-inflammatory response, and restored Hes-1 and β-catenin protein levels, in the crypts. Conclusion: The energy disruptor 2-DG mitigates bacterial infection and its responsive hyperplasia/colitis, indicating its utility as a mitigator of infection/IR-induced GI-damage.